'Lower leverage puzzle' in China's listed firms: an empirical study based on firm efficiency. (1st January 2012) - Zhang, Xindong; Ni, Ling; Chen, Yiping
This paper attempts to interpret 'lower leverage puzzle' in China's listed firms from the perspective of firm efficiency. It investigates the relationship between firm efficiency and capital structure based on a sample study of 1, 000 firm-year panel data of public firms in Shanghai Stock Exchange from 2004–2008. The findings show that between them two there exists a significant reversal exponential relationship, and also indicate that the 'lower leverage' is practically a natural choice of higher efficiency firms. Furthermore, it is suggested that the development stage of security market should be taken into consideration of the capital structure theory.